A New Method for Adjusting Setting Angle of Rotor Blade for Axial Fan in Wind Tunnel (Xibei Gongye Daxue Xuebao, 2019)
Combining the fan aerodynamic efficiency with the wind tunnel pressure loss coefficient, a new equation which points out the inherent relationship of the fan blade setting angle, fan rotating speed and gas flow rate in wind tunnel circuit is derived according to the two-dimensional flow theory of the axial fan rotor blades and the aerodynamic characteristics of the low speed wind tunnel. So a new method for setting angle adjustment of fan rotor blade to satisfy the fan performance at off-design point by getting the test results of fan operation parameters but without the fan total pressure rise in the low speed wind tunnel is developed. Flowing the new method, the setting angle adjusting value of fan rotor blade was provided only with the fan rotating speed and flow velocity in the test section of a low speed wind tunnel directly before the fan setting angle altered, the adjusting target was achieved by the new blade setting angle successfully and the time and cost of the wind tunnel commissioning test were saved. The test results show that, after increasing the fan rotor blade setting angle by 4.5 degrees, when the flow velocity in the wind tunnel test section reaches 60 m/s, the fan rotating speed is 570 r/min, the deviation from the predicted fan rotating speed value of 575 r/min is 0.9%. For the same test section flow velocity, the predicted value of the fan rotating speed is in a good agreement with the real value, it proves that this method is reliable and accurate in practical application.